2019
DOI: 10.1186/s12974-019-1492-6
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin suppresses amyloid-β oligomer (AβO)-induced inflammatory response of microglia via AdipoR1-AMPK-NF-κB signaling pathway

Abstract: Background Microglia-mediated neuroinflammation is important in Alzheimer’s disease (AD) pathogenesis. Extracellular deposition of β-amyloid (Aβ), a major pathological hallmark of AD, can induce microglia activation. Adiponectin (APN), an adipocyte-derived adipokine, exerts anti-inflammatory effects in the periphery and brain. Chronic APN deficiency leads to cognitive impairment and AD-like pathologies in aged mice. Here, we aim to study the role of APN in regulating microglia-mediated neuroinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 108 publications
(126 reference statements)
7
67
0
Order By: Relevance
“…Nevertheless, the mechanism explaining the relationship between ADPN and impaired cognitive function is often related to the inflammatory cascade. More authors theorized that serum ADPN levels could indirectly influence cognitive performances through the modulation of several interrelated systemic factors and in particular the inflammation cascade [41]. Indeed, Jian et al demonstrated that ADPN suppressed inflammatory response of microglia to amyloid-β oligomer (AβO) and ADPN deficiency may aggravate microglia-mediated neuro-inflammation in AD mice [41].…”
Section: Adiponectin and Mild Cognitive Impairment (Mci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the mechanism explaining the relationship between ADPN and impaired cognitive function is often related to the inflammatory cascade. More authors theorized that serum ADPN levels could indirectly influence cognitive performances through the modulation of several interrelated systemic factors and in particular the inflammation cascade [41]. Indeed, Jian et al demonstrated that ADPN suppressed inflammatory response of microglia to amyloid-β oligomer (AβO) and ADPN deficiency may aggravate microglia-mediated neuro-inflammation in AD mice [41].…”
Section: Adiponectin and Mild Cognitive Impairment (Mci)mentioning
confidence: 99%
“…The involvement of ADPN in AD is poorly understood, with divergent results showing a decrease [39,42], increase , or no significant changes [40][41][42][43][44]. However, in the past few years, several studies show the ADPN neuroprotective properties [1].…”
Section: Adiponectin and Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Increased NO reduces platelet aggregation and elevates vasodilation regulating cerebrovascular microcirculation. In addition, APN could suppress amyloid-β in mice (Jian et al, 2019). Waragai et al (2016) have suggested a possible positive effect of APN by finding that higher cerebrospinal fluid (CSF) level of APN is related with lower amyloid and tau burden.…”
Section: Hypertensionmentioning
confidence: 99%
“…Lecompte et al (2017) found that APN retained its anti-inflammatory feature in dystrophic muscle by activating the AdipoR1-AMPK-SIRT1-PGC-1αpathway in mice. Besides, Jian et al (2019) demonstrated that APN suppressed inflammatory response of microglia to amyloid-β oligomer (AβO) and APN deficiency may aggravate microglia-mediated neuroinflammation in AD mice. In patients with severe carotid stenosis, APN's negative association with glucose, insulin, and intraplaque inflammatory markers was observed (Liberale et al, 2018).…”
Section: Anti-neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation